What remains of the territory in the era of global flows? (Ciudades, 2017)
Massive mobilization of energy and material resources has enabled economic integration among remote areas which were previously autonomous and relatively self-sufficient. Traditional models used for studying the territory on the basis of local resources are no longer effective to describe the new reality. Today the territories have come to serve a global world-system, forgoing their internal complexity and becoming mere infrastructural support of global flows. Faced with the uncertainty that threaten the global system itself, a defensive strategy should focus on preserving those local resources that can provide some flexibility and autonomy to territories.
Keywords: spatial planning; globalisation; material flows; local resources; sustainability